HUBUNGAN TINGKAT KECUKUPAN ENERGI, AKTIVITAS FISIK, DAN PERSENTASE LEMAK TUBUH DENGAN KEJADIAN OBESITAS PADA PEKERJA WANITA (Studi pada Perusahaan Makanan Ringan di Semarang) - Radix Cita Mafngula Nandar; Siti Fatimah Pradigdo; Suyatno Suyatno (Jurnal Kesehatan Masyarakat (Undip), 2019)
The prevalence of obesity in women is higher than men. This is caused by high energy intake, low activity level, hight percentage of body fat, and use kind of contraception hormonal. This study aimed to determine the relationship between energy sufficiency level, physical activity, and percentage of body fat with incidence of obesity in women workers. It was a observational research with cross sectional design. The study population was 130 female workers and a sample of 52 people were selected by random sampling. This study uses primary data which includes: anthropometry (weight and height), respondent characteristics, nutritional consumption survey (24-hour recall), and physical activity using Physical Activity Ratio (PAR). Data analysis was performed using the chi square test. The results shawn majority of women workers included in obese (BMI>27,0) was 73.1%, high energy sufficiency level (≥100% RDA) was 67.3%, mild physical activity (1,40 - 1,69) was 82.7%, and high percentage of body fat (≥32%) was 65.4%. The analysis showed that there was a relationship between energy sufficiency level and percentage of body fat, between percentage of body fat and obesity (p<0.05). There was no relationship between physical activity and percentage of body fat, and between hormonal contraception with obesity (p≥0.05). It is expected that women workers can monitor their weight by paying attention to the intake of food consumed and increase physical activity regularly.